2019
DOI: 10.3390/robotics8020040
|View full text |Cite
|
Sign up to set email alerts
|

The Auto-Complete Graph: Merging and Mutual Correction of Sensor and Prior Maps for SLAM

Abstract: Simultaneous Localization And Mapping (SLAM) usually assumes the robot starts without knowledge of the environment. While prior information, such as emergency maps or layout maps, is often available, integration is not trivial since such maps are often out of date and have uncertainty in local scale. Integration of prior map information is further complicated by sensor noise, drift in the measurements, and incorrect scan registrations in the sensor map. We present the Auto-Complete Graph (ACG), a graph-based S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…A recent work [22] uses prior maps taken from emergency maps to build graph-based SLAM representations. The method, which extends that of [23], merges the information from sensors and a prior map into a representation of the environment and corrects errors both in sensor readings and the prior map.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent work [22] uses prior maps taken from emergency maps to build graph-based SLAM representations. The method, which extends that of [23], merges the information from sensors and a prior map into a representation of the environment and corrects errors both in sensor readings and the prior map.…”
Section: Related Workmentioning
confidence: 99%
“…Our focus is on exploration performance and not on the quality of the produced map (as in [22]), but the relationships between the two approaches could be further investigated.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In another scenario, sketch maps can be used to enhance existing prior maps, e.g., emergency maps. Working with Dortmund's firemen, we identified that they have access to emergency maps that they use to direct their operations [39]. However, while firemen are proficient with emergency maps, other people may not be, especially in situations of stress.…”
Section: Applicationsmentioning
confidence: 99%
“…Furthermore, we previously developed the Auto-Complete Graph (ACG) method [39] to integrate an emergency map into the robot's Simultaneous Localization and Mapping (SLAM). By first matching a sketch map to an emergency map using URSIM and then integrating the emergency map in the SLAM using the ACG method, the information of the sketch map could be included in the robot's map during exploration and used to navigate to points of interest, both by sketching a trajectory or autonomous navigation.…”
Section: Applicationsmentioning
confidence: 99%